Pertumbuhan Stek Tanaman Kebiul (Caesalpinia sp.) dengan Pemberian Ekstrak Bawang Merah (Allium cepa) dan Taoge Kacang Hijau (Vigna radiata) - Widia Gusti; Deni Parlindungan; Ika Saputri; Reti Novianti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aimed to measure the effect of red onion extract (Allium cepa) and green bean sprouts (Vigna radiata) on the growth of kebiul plants through cuttings with a comparison of synthetic growth regulators (Rootone-F) and control (without treatment). The research method used RAL (4 treatments, 12 replications) with an observation time of 6 weeks (12 observations) and measurements were made in the afternoon. Observation parameters were the number of seedlings growing, the number of shoots, time of shoot growth, shoot growth rate and the number of leaves. The results showed that the treatment with onion extract and mung bean sprouts better responded to the number of seedlings grown, number of shoots, shoot growth time, shoot growth rate and number of leaves compared to Rootone-F treatment and control. In conclusion, the administration of onion extract and mung bean sprouts could accelerate the growth of kebiul cuttings. Keywords: Shallots, Kebiul, Cuttings, Green Bean Sprouts